2023
DOI: 10.3126/jgmcn.v16i1.53645
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption among young school children in Pokhara, Kaski: A cross-sectional study

Abstract: Introduction: Low intake of fruit and vegetable (F&V) increased the risk of non-communicable diseases, followed by disability and death. The fact that many diseases in adulthood have their origins in habits formed during childhood is undeniable. Therefore, the study assessed the prevalence of fruit and vegetable consumption among young schoolchildren aged 5 to 9 years. Methods: A cross-sectional study was carried out among 352 children from March 8 to September 4, 2020. The multistage sampling method was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Last but not least, our findings imply that the socioeconomic status (education, work experience and income) of parents is consistently associated with the nutritional status and F/V consumption of children. In children with low-educated parents compared to their peers, those with higher education levels had a greater daily consumption rate of F&V. Also, children of parents with a high family income had higher odds of consuming more F&V [37,43,[49][50][51][52][53][54][55]. Nevertheless, in Attorp's and de Jong's research, there was nothing similar to the abovementioned studies, as they found that parents' income and education were not significantly associated with their children's F&V consumption [56,57].…”
Section: Studies With Children/parents and Fruit/vegetable Consumptionmentioning
confidence: 88%
See 1 more Smart Citation
“…Last but not least, our findings imply that the socioeconomic status (education, work experience and income) of parents is consistently associated with the nutritional status and F/V consumption of children. In children with low-educated parents compared to their peers, those with higher education levels had a greater daily consumption rate of F&V. Also, children of parents with a high family income had higher odds of consuming more F&V [37,43,[49][50][51][52][53][54][55]. Nevertheless, in Attorp's and de Jong's research, there was nothing similar to the abovementioned studies, as they found that parents' income and education were not significantly associated with their children's F&V consumption [56,57].…”
Section: Studies With Children/parents and Fruit/vegetable Consumptionmentioning
confidence: 88%
“…Findings showed that most parents and children were not consuming the recommended amount of fruits and vegetables [29][30][31][32][33][34][35][36][37]. On the other hand, in Eliason's and Charneca's studies, it appeared that most children, especially the younger age groups, met WHO guidelines for the daily amount of fruit.…”
Section: Studies With Children/parents and Fruit/vegetable Consumptionmentioning
confidence: 99%